2010
DOI: 10.1016/j.cellimm.2009.09.006
|View full text |Cite
|
Sign up to set email alerts
|

The ACE inhibitors enalapril and captopril modulate cytokine responses in Balb/c and C57Bl/6 normal mice and increase CD4+CD103+CD25negative splenic T cell numbers

Abstract: Increasing evidence implies beneficial effects of angiotensin-converting enzyme (ACE) inhibitors beyond those of their original indications to control hypertension. One of the most attractive non-hemodynamic properties of ACE inhibitors is their ability to regulate cytokine production. The mechanism(s) underlying the role of ACE inhibitors on cytokine synthesis are not well understood but they have traditionally been attributed to the inhibition of angiotensin (Ang) II formation. In fact, it has been extensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…Captopril has been shown to express immune-regulating, antioxidant and anti-inflammatory properties. [34] In agreement with these studies, our results showed that depressing cytokine expression is associated with improved cardiac function.…”
Section: Discussionsupporting
confidence: 81%
“…Captopril has been shown to express immune-regulating, antioxidant and anti-inflammatory properties. [34] In agreement with these studies, our results showed that depressing cytokine expression is associated with improved cardiac function.…”
Section: Discussionsupporting
confidence: 81%
“…ACE inhibition is clinically associated with reduction of urinary MCP-1 levels and in pre-clinical models of remnant kidney disease it has been shown to prevent local proliferation of macrophages and myofibroblasts in the kidney [57]. However, Albuquerque et al showed that enalapril treatment potently increases the number of CD4 + T cells in the spleen together with the increasing production of IL-2 and IL-10 [58]. Our observation that the overall kidney associated leukocyte number, specifically the CD4 + /CD8 + T cells, is increased after enalapril treatment in both db/db and STZ treated mice demonstrates that the angiotensin II blockade overall seems to favor proliferation or attraction of lymphocytes specifically in advanced disease.…”
Section: Discussionmentioning
confidence: 98%
“…Tumor-bearing mice were administered captopril in their drinking water at 1, 10, 50, or 100 mg/kg/d; these are typical, murine therapeutic dosages. 23,24 Captopril attenuated tumor growth in a dose-dependent fashion ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%